‘Who is My Jung?’ The Progressive, though Sometimes Ambivalent, Expansion of Jung's Idea of the Collective Unconscious: From an ‘Unconscious Humanity’ to - in all But Name - the Soul of the World - Cashford, Jules (Journal of analytical psychology, 2018)
This paper discusses Jung's idea of myth as a projection of the collective unconscious, suggesting that the term ‘projection’ separates human beings from nature, withdrawing nature's life into humanity. Jung's discovery of a realm independent of consciousness - in conversations with his soul in The Red Book, and in synchronicity, began a dialogue which finally brought him, through the Alchemical Mercurius, closer to the idea of a world-soul.